La transdisciplinarité à l’épreuve de l’engagement, réflexions à partir de l’application de la méthode photovoice - Anastasia-Alithia Seferiadis (VertigO)
While “transdisciplinarity” is a term that is increasingly being used, particularly with regard to its potential to shed light on complex issues as highlighted by sustainability sciences, the contours of its definitions remain unclear. Based on my experience of mobilizing a specific participatory research tool based on photography – photovoice – I propose an analysis of transdisciplinarity through practice. A field work analysis will show how this scientific approach offers a critical approach to the construction of knowledge through a rigorous (in)discipline. Transdisciplinarity thus appears as a transformative epistemology, producing knowledge that can cause transformations at the level of socio-ecosystems, but also as an epistemological transformation, it is indeed co-constructed knowledge that mobilizes holistic, iterative, and relational modes of reasoning. The vision of transdisciplinarity developed in this article places it within an engaged perspective of deconstructing the power relations inherent in knowledge co-construction processes.